Effects of various remineralizing agents on the outcome of post-orthodontic white spot lesions (WSLs): a clinical trial - Singh, Sombir (Prog Orthod, 2016)
BACKGROUND: One of the most undesirable side effects of comprehensive orthodontic treatment is white spot lesions (WSLs). Despite many attempts at prevention of WSLs, its prevalence remains very high on debonding. There are many agents like fluoride toothpastes, fluoride varnishes, and fluoride mouth rinses, and casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) is frequently used for the remineralization of WSLs. However, there is no consensus in the literature with respect to the success rates of these agents. Thus, the present study was designed to evaluate the efficacy of fluoride toothpaste alone and in combination with fluoride varnish and CPP-ACP plus crème in the remineralization of post-orthodontic WSLs. METHODS: Forty-five subjects in the age range of 16–25 years having at least one post-orthodontic WSL were included in the study. All the subjects were randomly divided into three groups (toothpaste group, varnish group, and CPP-ACP group). The efficacy of various remineralizing agents on the remineralization of WSLs was evaluated clinically and by DIAGNOdent immediately after debonding and subsequently after 1, 3, and 6 months of their use. RESULTS: Twice daily use of fluoride toothpaste alone had no significant effect on remineralization of WSLs at various intervals of observations (P = 0.078). Application of fluoride varnish along with twice daily use of fluoride toothpaste for 6 months significantly decreased the severity of WSLs (P < 0.01). Twice daily use of CPP-ACP plus crème along with fluoride toothpaste had significant effect on remineralization of WSLs at the end of 6 months of observation (P < 0.05). Between the group comparison showed that the mean visual and DIAGNOdent scores at various time intervals of observations were decreased more when fluoride varnish and CPP-ACP crème were used in addition to daily use of fluoride toothpaste, but the differences were not statistically significant (P > 0.05). CONCLUSIONS: The use of fluoride varnish and CPP-ACP plus crème in addition to twice daily use of fluoride toothpaste had no additional benefit in the remineralization of post-orthodontic WSLs.